2014
DOI: 10.1152/ajplung.00210.2013
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin delivery by osmotic minipump: similarity to human scleroderma interstitial lung disease

Abstract: Lee R, Reese C, Bonner M, Tourkina E, Hajdu Z, Riemer EC, Silver RM, Visconti RP, Hoffman S. Bleomycin delivery by osmotic minipump: similarity to human scleroderma interstitial lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
71
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 25 publications
8
71
2
Order By: Relevance
“…In agreement with previous reports that a murine model of lung fibrosis induced by implanting an osmotic minipump containing BLM, 19,20 we confirmed this finding based on our observation of the pathological changes in the lung. Compared with the lung changes induced by intratracheal administration or multiple sc injections of BLM, BLM given by osmotic minipump led to a greater increase in lung hydroxyproline and much extensive pleural surface involvement.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous reports that a murine model of lung fibrosis induced by implanting an osmotic minipump containing BLM, 19,20 we confirmed this finding based on our observation of the pathological changes in the lung. Compared with the lung changes induced by intratracheal administration or multiple sc injections of BLM, BLM given by osmotic minipump led to a greater increase in lung hydroxyproline and much extensive pleural surface involvement.…”
Section: Discussionsupporting
confidence: 93%
“…22 A very recent study also mentioned the thickening of skin following the implantation of osmotic minipumps with BLM. 19 We here further described the time course of changes in skin morphology, cutaneous infiltrates, and pro-inflammatory cytokine expression following the treatment of minipumps with BLM in detail. Thus, this modified murine model of SSc could be helpful to understand the underlying mechanisms of SSc and search for new therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bleomycin has been claimed to have minimal immunosuppressive activity and low hematopoietic toxicity, chemotherapy using bleomycin is often complicated by interstitial pulmonary fibrosis (Kawai and Akaza, 2003;Kim et al, 2010). Thus, bleomycin has been widely used in making pulmonary fibrosis animal models (Lee et al, 2014). Repetitive administrations of bleomycin by intraperitoneal or intravenous injection induce pleural and subpleural fibrosis, which is similar to what is seen in human IPF (Mouratis and Aidinis, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that administration of a high dose of bleomycin often leads to lethal lung injury and pulmonary fibrosis in human patients, as well as in rodent (Hoshino et al, 2009). Therefore, it has been widely used in making pulmonary fibrosis animal models (Lee et al, 2014). The bleomycin model has the advantage that it is quite easy to perform, widely accessible and reproducible, and therefore fulfills important criteria expected from a good animal model (Mouratis and Aidinis, 2011).…”
Section: Discussionmentioning
confidence: 99%